Safety and efficacy of intracoronary artery administration of human bone marrow-derived mesenchymal stem cells in STEMI of Lee-Sung pigs—A preclinical study for supporting the feasibility of the OmniMSC-AMI phase I clinical trial - Chen, Wannhsin; Hou, Chun-Hsiang; Chen, Yi-Ling; Shen, Hsin-Hsin; Lin, Chen-Hsuan; Wu, Cheng-Yi; Lin, Meng-Hsueh; Liao, Chih-Ching; Huang, Jun-Jae; Yang, Chi-Yu; Li, Yi-Chen; Yip, Hon-Kan (Frontiers in Cardiovascular Medicine, 2023)
Background: This study tested whether early left intracoronary arterial (LAD) administration of human bone marrow-derived mesenchymal stem cells (called OmniMSC) in acute ST-segment elevation myocardial infarction (STEMI) in Lee-Sung pigs induced by 90-mins balloon-occluded LAD was safe and effective. Methods and Results: Young-male Lee-Sung pigs were categorized into SC (sham-operated-control, n=3), AMI-B (STEMI + buffer/21cc/administered at 90-min after STEMI, n=6) and AMI-M (AMI + HBMDMSCs/1.5x107/administered at 90-min after STEMI, n=6) groups. By 2 and 5 months after STEMI, the cardiac magnetic-resonance-imaging (MRI) demonstrated that the muscle-scar-score (MSS) and abnormal cardiac muscle exercise score in infarct region were significantly increased in AMI-B than in the Sham that were significantly reversed in AMI-M, whereas the left ventricular function (LVEF) by each month (from 1 to 5) displayed an opposite pattern of MSS among the groups (all p<0.001). By 5-months, histopathological findings of infarct and fibrosis areas and isolectin-B4 exhibited an identical pattern, whereas the cellular expressions of troponin-I/troponin-T/von-Willebrand factor exhibited an opposite pattern of MSS among the groups (all p<0.001). The ST-segment resolution (>80%) was significantly earlier (estimated after 6h-AMI) in group AMI-M than in group AMI-B (p<0.001). The protein expressions of inflammation (IL-1β/TNF-α/NF-κB)/oxidative-stress (NOX-1/NOX-2/oxidized protein)/apoptosis (cleaved-caspase-3/cleaved-PARP)/DNA-damage (γ-H2AX) displayed an identical pattern to MSS among the groups, whereas the protein expressions of angiogenesis factors (SDF-1α/VEGF) were significantly and progressively increased from SC, AMI-B to AMI-M group (all p<0.001). Conclusion: Early intra-LAD transfusion of OmniMSC treatment effectively reduced infarct size and preserved LV function in porcine STEMI.